“To find a direction for life” : viewpoints for students’ development of educational orientation during VALMA-studies - Toikka, Ami (2022)
The purpose of this research was to get a deeper understanding of the overall learning process students go through during their preparatory training for vo-cational education (VALMA) studies. The aim was to better understand the significance of VALMA- training programme in the development of students’ educational and career orientation. The research questions were how VALMA-students’ starting points vary, and how does the students’ educational orienta-tion develop during VALMA-studies. This study was approached from two theoretical perspectives, career and educational decision making and student agency using narrative, text-based data collection method. In formulating the research questions, the underlying thought was biphasic data collection procedure. Data was collected from two different adolescent VALMA-groups, twice during one academic year. A thematical analysis was used to analyse and interpret the data. Findings of this study show, that even though the starting points of the students would vary, it does not effect on the learning process negatively. Students’ orientation to learning was able to develop in various ways during VALMA-studies. Results demonstrate how VALMA studies had personal significance for the students. The importance of daily routine, social contacts and positive environment emerged from the study. Results indicate, that VALMA-studies had helped the students in their goal of finding own field.